ARM based Data Acquisition System for Physics Experiments - Bhadane, Pravin; Bhangale, Suchita (International Journal of Computer Sciences and Engineering, 2019)
The technological evolution in VLSI design plays important role in the field of microelectronics. The microelectronic device such as microcontroller is widely used in the data acquisition system (DAS). The DAS for the physics laboratory application can be developed with microcontroller like Advanced RISC Machine (ARM) and supporting hardware. This paper comprises detail explanation about the data acquisition system using ARM 7 LPC -2148 and C – language programs. The system includes peripherals such as ADC, DAC, keypad, character LCD and external interrupt. The software programs for interfacing them with microcontroller are written and prescribed here for the first time learner. The physics experimental parameters like temperature, pressure can be acquired by the developed DAS.